2018
DOI: 10.1002/mus.26196
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mesenchymal stromal cells on type 1 diabetes mellitus rat muscles

Abstract: MSCs can reduce muscle and functional complications that result from type 1 DM in rats. Muscle Nerve 58: 583-591, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…In diabetic rats, motor activity, CSA and the number of fibres were reduced. The reduction of myofibres and muscle mass was associated with both increased protein degradation and decreased protein synthesis in skeletal muscles causing the muscle weakness in T1D. The more pronounced atrophy of white muscles is observed in muscle wasting disorders, and the responses of red muscles to STZ and/or MSC therapy may differ .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In diabetic rats, motor activity, CSA and the number of fibres were reduced. The reduction of myofibres and muscle mass was associated with both increased protein degradation and decreased protein synthesis in skeletal muscles causing the muscle weakness in T1D. The more pronounced atrophy of white muscles is observed in muscle wasting disorders, and the responses of red muscles to STZ and/or MSC therapy may differ .…”
Section: Discussionmentioning
confidence: 99%
“…However, the observed strong positive correlation between CSA and motor activity is noteworthy. It has been previously reported that the walking performance and motor dysfunction in diabetic rats are associated with skeletal muscle fibrosis and decreased motor units and that the local and systemic transplantation of MSCs contribute to myogenesis, cellular differentiation in muscle inflammatory and degenerative condition models improving the repair process. However, the molecular mechanism of action of MSCs on muscle fibre repair and motor function improvement is not fully understood …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment consists mainly of protective lung ventilation strategies and early fluid resuscitation. Despite the continuous improvement in treatment methods, the mortality rate remains as high as 40%-60% [ 2 ]. The lack of specific etiological treatment measures is an important factor in the high mortality rate of ARDS.…”
Section: Introductionmentioning
confidence: 99%
“…MSCs can also secrete a variety of cytokines to exert anti-inflammatory and repair effects. In recent years, a large number of studies have shown that MSCs can effectively treat a variety of diseases, including myocardial injury and diabetes [ 1 , 2 ]. In ARDS, MSCs exert a significant therapeutic effect, both in animals and humans, showing its unique and excellent anti-inflammatory and antidamage properties [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%